Analisis Faktor-faktor yang Mempengaruhi Kunjungan Lanjut Usia di Sentra Pelayanan Kesehatan Masyarakat - Menap Menap; Baiq Maryam; Sastrawan Sastrawan (Bioscientist : Jurnal Ilmiah Biologi, 2021)
The study aims to analyze the factors that influence elderly visits at public health service centers. This research is a quantitative descriptive study with a cross sectional approach. The population in this study was as many as 2.000 elderly people in Sikur District of East Lombok Regency. The sample was selected randomly sampling, determined by the formula Slovin (10% leeway percentage), with a sample of 98 elderly people. The instruments used in the form of questionnaires about factors that affect elderly visits include environmental support, perception, knowledge, character, alternative activities, and the management of public health service centers. Data collection is done through the dissemination and filling of questionnaires by the elderly related to factors that affect visits. The results showed that factors affecting elderly visits include: 1) environmental support, sig value. (ρ = 0.000); 2) perception, sig value. (ρ = 0.015); 3) knowledge, sig value. (ρ = 0.013); 4) character, sig value. (ρ = 0.125); 5) alternative activities, sig values. (ρ = 0.002); and 6) posyandu management, sig value. (ρ = 0,000). Thus, it can be stated that factors such as environmental support, elderly perception, elderly knowledge, alternative elderly activities, and management affect elderly visits in the center of public health services in Sikur District of East Lombok Regency.